Investigating the application value of the “Forward-Deployed Position” model in operating room support by the central sterile supply department - Qian Yang; Yun Wang; Mingjun Wu (PLoS ONE, 2026)
Objective To investigate the application effects of the “Forward-Deployed Position” model in operating room support provided by the Central Sterile Supply Department (CSSD). Methods This study employed a historical control design. Data from the period when the “Forward-Deployed Position” model was implemented in our hospital in 2024 were set as the observation group, while data from 2023 under the traditional model served as the control group. The two groups were compared regarding indicators including the instrument re-cleaning rate, packaging qualification rate, clinical department satisfaction, and on-time start rate for the first scheduled surgery of the day. Results Compared with the control group, the observation group demonstrated a significant increase in the packaging qualification rate (99.05% vs 98.05%), clinical department satisfaction, and the on-time start rate for the first scheduled surgery (95.05% vs 85.63%), alongside a significant decrease in the instrument re-cleaning rate (0.37% vs 1.05%). All these differences were statistically significant (p < 0.05). Conclusion Provided that implementation conditions such as human resources are fully considered, the “Forward-Deployed Position” model can effectively enhance the work quality of the CSSD and the efficiency of surgical support. Its successful implementation relies on a specialized team and sustained inter-departmental collaboration, offering a valuable reference for optimizing surgical workflow management.